Academic Discourse on Higher Education in Lithuania – Towards Neoliberalism - Girkontaitė, Agnė (Acta Paedagogica Vilnensia, 2025)
The purpose and challenges of higher education remain a widely debated topic in both public and academic discourse, often focusing on critiques of higher education’s shift toward the neoliberal ideology. There is an extensive body of literature on academic managerialism, audit culture, new public management, and other trends of the market logic in higher education. Despite this, there is a notable lack of comprehensive research on the position and perspectives of higher education researchers in Lithuania. In an attempt to address this gap, the present paper, grounded in the tradition of critical discourse analysis, explores the findings of a qualitative analysis of research publications on higher education in Lithuania spanning the years from 2005 to 2023. The study highlights that the Lithuanian academic discourse on higher education is largely shaped by the uncritical adoption of the knowledge-based economy discourse, predominantly derived from the Bologna Process documents. This dominant discourse frames higher education’s primary goal as the preparation of a highly skilled, internationally competitive workforce aimed at improving the European economic competitiveness. While this perspective prevails, it is supplemented by additional elements unique to the Lithuanian context. These include an emphasis on cultural and national identity education. Furthermore, there are occasional critical reflections on this dominant narrative or specific aspects of its implementation. However, such critiques are relatively sparse, suggesting a need for a more nuanced and critical engagement with the overarching discourse in Lithuanian higher education research.
Keywords: higher education; academic discourse; neoliberalism; critical discourse analysis